Municípios Lindeiros na microrregião de Toledo e a aplicação de royalties - Xavier, Damião (2013)
This study aimed to analyze the micro-region of Toledo, Paraná State in the period 2000 to 2010, focusing in a special issue of royalties paid out to Municipalities Lindeiros Lake Itaipu. This micro-region was the scene during the last decades of intense changes of physical and socioeconomic, motivating the need for more detailed understanding about some information about the reality of it compared to the factors that generated the royalties and their possible applications. Through methodological procedures based on literature surveys along with research in loco, it was observed that the nine municipalities belonging to the micro-region of Toledo had considerable increases in their income from the receipt of royalties. It was observed that most of the cities studied have its economy directly related to transfers of this "benefit" and the end of the financial compensation paid by Itaipu Binacional affect investments in infrastructure, both public and private, because few municipalities be able to continue offering attractive services and quality to the population. However, note that Marechal Cândido Rondon has been highlighted by presenting apparently better financial investment without the revenue stemmed from royalties because it has a dynamic economy that consolidates between industry and agriculture. The municipalities demographically smaller and suffer the loss of wetland area that could have been designed to agriculture also suffered significant losses, beyond the territorial area, which reflected in other sectors of the economy, as in the case of the municipality of Guaíra to the detriment of the end of the Seven Falls, suffered from reduced tourism and thus gains the local market. These issues are problematized at work and on which they sought to bring some contribution.